Potentiality of virtuality in the academic formation of students of the faculty of health sciences. University of Guayaquil - Rebolledo Malpica, Dinora; Granados Romero, John (Revista Universidad de Guayaquil, 2023)
Virtuality became the ideal strategy during the health crisis due to SARS-CoV.2 to shovel the loss of face-to-face attendance in educational environments and especially higher education. In this sense, the training of human talent in health sciences, with its unique nature in acquiring practical and humanized skills to care for patients in situations of vulnerability. It is solved with these virtual strategies. The methodology used in this study was based on a systematic review of the state of knowledge on the potential of virtuality in training in health sciences, high-impact articles are recorded consulted in annealed and indexed databases, with the use of keywords, medical education, virtuality, Pandemics. The analysis is performed with the qualitative technique of content analysis. The results are presented, according to the meaning attributed in the findings found in the articles analyzed. A discussion was generated that leads to the conclusions on the leading role of virtual education in health sciences and higher education training in general and how the strategy of combining virtuality with other forms of teaching such as simulation, recorded real cases and others, is the ideal key to promote the acquisition of necessary skills in the training of student’s health sciences of the University of Guayaquil